Distance Tutoring: A Study on the Dimensions of Mediation (Research, Society and Development, 2019)
Distance education has been gaining more space in the educational field, thus, diversified methodologies are elaborated in search of possibilities that leverage the experiences of this teaching modality, involving all the actors of this process as teachers and tutors. This article presents a clipping of a master's dissertation that analyzed the tutors 'understanding about mediation in the pedagogical, affective and operational dimensions, as it understands the important mediation process for the students' permanence and completion in the enrolled courses. We rely on research conducted by Masetto, Almeida, Moran, Silva, Freire and also on quality references for distance education in conceptualizing mediation. In this article, we approach the concept of mediation resulting from one of the analyzes performed with the tutors of a distance education institution in the country. The methodology used in this research is exploratory, qualitative in nature to understand the mediation of tutors as an inseparable part of distance education. The results showed that tutors sought through mediation to motivate and engage their students in the courses.